If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2x+4=(3x+6
We move all terms to the left:
6(2x+4-((3x+6)=0
| 1)y+6=20 | | T=4s+4.03 | | T=4s+4.03s | | 220.00+0.15m=299.50 | | 8(x-5)+29=7x-6 | | 8(x-2)+3=8x-12 | | 6(x-8)+40=6x-8 | | -10−4g=-6g | | 18x−3x^2=0 | | -7v+3=-7−6v | | -5k=-7k−10 | | X(x-1)=200 | | 2−7u=-5u+6 | | 7r+21=44r | | 5r+10=-5+2r | | 29=257-x | | 4k+10=5k | | 10r=8+8r | | 14+25f=35+16f | | -12p39=11(p+14) | | -2−6v=-5v | | (d/5)+3D-10=(1/3)d+33 | | D/5+3D-10=(1/3)d+33 | | 1/6y-4=-11 | | -3b=-2b−9 | | 2h=h−8 | | 1+8x+3=-12 | | -13=5x+8x | | -9y=-8−8y | | -y=8+3y | | 7m=6m+8 | | -10−1=9w |